ANALISIS USAHA TERNAK AYAM PETELUR AZ DI DESA TALUMBINGA KECAMATAN SABULAKOA KABUPATEN KONAWE SELATAN - Titop, Herman; H.M., Suyuti; Zakariah, Ahmad (Sultra Journal of Economic and Business, 2022)
This study aims to determine the level of profit and feasibility level of AZ Laying Chicken Farming in Talumbinga Village, Sabulakoa District, Konawe Selatan Regency.The results of this study indicate that the AZ Layer Farming Business Income Analysis in Talumbinga Village, Sabulakoa District, South Konawe Regency is profitable and feasible to develop.The farmer's profit generates a net income of IDR 84,715,000 per year or IDR 7,059.583 per month and a B/C-Ratio of 1.44.